A reclaimed rubber composite modified emulsified asphalt based on induced oxidative degradation and a preparation method thereof
Patent Information
- Application Number
- CN202610767201.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-29
- Publication Date
- 2026-10-30
AI Technical Summary
[0027]1.本申请无需采用现有技术中高耗能的密炼+螺杆挤出造粒设备,也无需再水相中添加价格昂贵的自乳化水性环氧树脂,全程仅需在常规改性沥青设备中原位完成,工艺极简,制备成本降低约30%,成本大幅下降;
Abstract
Description
Technical Field
[0001] This application relates to the field of emulsified asphalt, and more specifically, to a reclaimed rubber composite modified emulsified asphalt based on induced oxidative degradation and its preparation method. Background Technology
[0002] Rubberized asphalt has been widely used in road engineering due to its excellent high and low temperature performance, fatigue resistance, and environmentally friendly disposal capacity for waste tires. However, with increasingly stringent environmental protection requirements and the promotion of cold-mix paving technology, preparing rubberized asphalt into emulsified rubberized asphalt has become an inevitable trend in the industry.
[0003] Currently, the industry faces a prominent technical contradiction between rheology and colloid dynamics in the preparation of emulsified rubber asphalt, especially when the rubber content reaches a high level (e.g., above 30%). Firstly, the swelling of high-content rubber powder in asphalt causes an exponential increase in the system viscosity. Conventional equipment (colloid mills) requires the asphalt viscosity upon entry to not exceed 1.0 Pa·s; otherwise, it will lead to mill blockage. If the processing temperature is significantly increased to reduce viscosity, it will cause the aqueous phase to boil, resulting in instantaneous emulsion demulsification.
[0004] Secondly, in order to forcibly reduce the viscosity of high-content rubber asphalt, existing technologies typically involve adding large amounts of rubber oil or using deeply desulfurized and degraded rubber. However, once the viscosity is reduced, due to the density difference between rubber particles (especially the carbon black within them) and asphaltene, in a low-viscosity fluid lacking spatial network constraints, the rubber particles will rapidly aggregate and float after emulsification, causing the emulsion to separate and break down within hours to days.
[0005] To address the aforementioned problems, existing technologies have explored various solutions. For example, existing technologies (such as patent application CN 114874459B) propose first mixing and granulating reclaimed rubber, SBS, and maleic anhydride using a screw extruder to prepare composite granules, which are then added to asphalt. The solution relies on the addition of expensive self-emulsifying waterborne epoxy resin to the aqueous phase (soap solution) to provide post-demulsification strength. However, this method of physical pre-granulation combined with aqueous phase thickening is not only cumbersome and energy-intensive, but also fails to fundamentally solve the thermodynamic instability of the asphalt phase itself.
[0006] Therefore, how to significantly reduce the macro viscosity of high-dosage rubber asphalt to meet emulsification conditions and construct an internal anchoring mechanism to resist rubber floating, without relying on expensive water-based resins or adding complex extrusion granulation processes, is a common technical problem that urgently needs to be solved in this field. Summary of the Invention
[0007] To address the aforementioned technical issues, this application provides a method for preparing reclaimed rubber-modified emulsified asphalt based on induced oxidative degradation. This method eliminates the complex physical pre-granulation process and aqueous thickening techniques, relying solely on the "induced degradation-polarity reconstruction-interfacial micro-crosslinking" mechanism within the pure asphalt phase to achieve excellent stability and road performance of high-content rubber-modified emulsified asphalt.
[0008] In a first aspect, this application provides a method for preparing reclaimed rubber composite modified emulsified asphalt based on induced oxidative degradation, which adopts the following technical solution:
[0009] A method for preparing reclaimed rubber-modified emulsified asphalt based on induced oxidative degradation includes the following steps:
[0010] S1. Preparation of high-content masterbatch: 30-40% of the total mass of the composite modified asphalt is mixed with the base asphalt and 10-15% of the total mass of the composite modified asphalt, and the mixture is subjected to high-speed shear swelling to prepare rubber modified asphalt masterbatch; the reclaimed rubber is a high-flowability reclaimed rubber with Mooney viscosity <20 obtained by heat-oxygen-chemical coupling induced oxidative degradation treatment of waste tire rubber.
[0011] S2. In-situ reaction: Add 4-6% SBS modifier to the masterbatch, and after shear development, cool to 160-170℃. Add maleic anhydride to carry out in-situ grafting reaction. After the system is stable, add 0.12-0.15% polyphosphoric acid to adjust the pH value and rheological properties of the asphalt phase.
[0012] S3. Interface micro-crosslinking anchoring: Sulfur is added to the system after S2 treatment, the amount of sulfur added is 0.05-0.06% of the mass of the base asphalt, and stirred at 160-170℃ for 1-2 hours to form a micro-crosslinking anchoring network between SBS, degraded reclaimed rubber and asphalt in the system without significantly increasing the macro viscosity, and the dynamic viscosity of the resulting composite modified asphalt at the emulsification temperature is controlled to be between 0.6-1.0 Pa·s;
[0013] S4. Shear emulsification: Prepare a soap solution containing an emulsifier and water, wherein the mass of the emulsifier accounts for 1.0-1.4% of the total mass of the reclaimed rubber composite modified emulsified asphalt. The composite modified asphalt obtained in S3 is sheared together with the soap solution to obtain the reclaimed rubber composite modified emulsified asphalt.
[0014] Preferably, in step S1, the induced oxidative degradation process includes: mixing waste rubber powder with an oxidizing plasticizer, and subjecting it to high-speed shearing at 180-200°C with air introduced to induce oxidative chain scission of rubber macromolecules; the oxidizing plasticizer is 2,2'-dibenzoylaminodiphenyl disulfide.
[0015] Preferably, in step S2, the maleic anhydride is directly added to the molten asphalt phase after the system is cooled to 160-170°C, and the reaction time is 0.5-1.5 h.
[0016] Preferably, in step S3, the sulfur forms weak chemical bonds only at the phase interface, and the resulting network yield stress is greater than the buoyancy of the carbon black phase precipitating and floating in the reclaimed rubber, thereby suppressing the segregation phenomenon after emulsification.
[0017] Preferably, in step S4, the emulsifier is a cationic emulsifier and / or an amphoteric emulsifier.
[0018] Preferably, in step S4, the shearing process conditions are as follows: the temperature of the composite modified asphalt is controlled at 150-165℃, and the emulsion flowing out after emulsification is immediately cooled with circulating water so that its discharge temperature does not exceed 70℃.
[0019] Preferably, the base asphalt is 70# heavy-duty asphalt or 90# heavy-duty asphalt for roads.
[0020] Through the above technical solution, this application first utilizes a "thermal-oxygen-chemical coupling induction" mechanism. During the masterbatch preparation stage, aromatic rubber oil and oxidizing plasticizers are used under 180-200℃ and aeration shear conditions to actively induce controlled oxidative chain scission of the crosslinked network and main chain of waste tire rubber. This step directly reduces the Mooney viscosity of the rubber to below 20, giving it extremely high fluidity and fundamentally solving the processing bottleneck of asphalt not being able to flow and pump through the colloid mill at ultra-high admixtures of 30-40%.
[0021] However, while rubber gains fluidity after degradation, it inevitably suffers from a loss of high-temperature elastic modulus. Simultaneously, the non-polar rubber / SBS system exhibits extremely high interfacial tension with the aqueous phase, making it highly susceptible to demulsification. This application addresses this by cooling the masterbatch after preparation and directly grafting maleic anhydride in the asphalt liquid phase. The maleic anhydride is not only grafted onto SBS but also precisely anchored at the broken chain ends of the degraded rubber, imparting strong hydrophilic polarity to the oil phase. Subsequently, polyphosphoric acid is added as a protic acid, forming strong hydrogen bonds with the polar groups of maleic anhydride. This in-situ chemical reaction is significantly different from the existing physical premixing granulation techniques. Without significantly increasing macroscopic viscosity, it effectively compensates for the modulus loss due to degradation and makes asphalt droplets more easily encapsulated by the aqueous phase.
[0022] Then, this application adds a specific amount of sulfur as a crosslinking agent to the system, which significantly overcomes the technical bias in the industry. It is generally believed in the art that sulfur should not be added to emulsified asphalt because conventional amounts of sulfur (>0.15%) will induce three-dimensional crosslinking, leading to a surge in viscosity and clogging of the colloid mill. However, this application strictly controls the amount of sulfur added and precisely explores an extremely narrow critical window for micro-crosslinking of 0.005-0.006%. At this ultra-low dosage, sulfur is insufficient to form a macroscopic three-dimensional dead crosslinking network (the macroscopic viscosity can still be controlled within the emulsifiable range of 0.6-1.0 Pa·s), but only forms a sparse "interfacial anchoring network" between the SBS, the interface of the degraded reclaimed rubber particles and the asphalt. The yield stress of this micro-network just offsets the buoyancy of the density difference between the degraded rubber (especially free carbon black) and the aqueous phase, trapping it inside the asphalt droplets and completely eliminating segregation and floating phenomena.
[0023] Finally, since maleic anhydride and polyphosphoric acid are introduced into the oil phase, the system is slightly acidic. Therefore, this application uses zwitterionic emulsifiers and / or cationic emulsifiers to form a double electric layer and steric hindrance at the oil-water interface for dual protection. The mill exit temperature is strictly controlled to ≤70℃ to prevent secondary thermal aggregation of the micro-crosslinked network in the high-temperature aqueous phase, thus ensuring the long-term storage stability of the emulsion.
[0024] Secondly, this application provides a reclaimed rubber composite modified emulsified asphalt prepared by the above-mentioned preparation method of reclaimed rubber composite modified emulsified asphalt based on induced oxidative degradation.
[0025] Preferably, the mass ratio of the asphalt phase to the water phase in the recycled rubber composite modified emulsified asphalt is 60:40, and the storage stability index of the recycled rubber composite modified emulsified asphalt after standing at room temperature for 5 days is ≤1.0%.
[0026] In summary, this application has the following beneficial technical effects:
[0027] 1. This application does not require the use of the energy-intensive internal mixing + screw extrusion granulation equipment in the prior art, nor does it require the addition of expensive self-emulsifying waterborne epoxy resin in the aqueous phase. The entire process can be completed in situ in conventional modified asphalt equipment, which simplifies the process and reduces the preparation cost by about 30%, resulting in a significant cost reduction.
[0028] 2. Even with a rubber content as high as 30-40%, this application can still stably control the dynamic viscosity of the pre-emulsified asphalt phase at 135℃ to 0.6-1.0 Pa·s, with excellent colloid mill throughput, breaking through the dosage limit and processing bottleneck.
[0029] 3. This application introduces a very low amount of sulfur as a crosslinking agent to form an interfacial micro-crosslinking network, which makes the storage stability index of the prepared reclaimed rubber composite modified emulsified asphalt ≤1.0% after standing at room temperature for 5 days. There is no carbon black floating or stratification, the softening point of the water evaporation residue reaches above 70℃, and the ductility at 5℃ reaches above 20cm. It takes into account both high deformation resistance and strong crack resistance, and has excellent anti-segregation storage stability. Detailed Implementation
[0030] The technical solution of this application will be further described in detail below with reference to specific embodiments and comparative examples, but this should not be construed as a limitation on the scope of protection of this application.
[0031] Unless otherwise specified, all raw materials used in this application are commercially available products.
[0032] In the following examples, Sinopec 70# heavy-duty road asphalt is used as the base asphalt for illustration;
[0033] The following explanation uses commercially available aromatic rubber oil as an example.
[0034] The following example uses 40-mesh waste tire rubber powder, which is pulverized at room temperature, as an illustration.
[0035] The SBS modifier is illustrated using a linear T6302 structure SBS modifier as an example;
[0036] The example of polyphosphoric acid with an effective mass fraction of 105% will be used for illustration.
[0037] The emulsifier used is an amphoteric emulsifier, specifically a commercially available betaine-based amphoteric emulsifier as an example.
[0038] In the following examples, the preparation of 100 kg of target recycled rubber composite modified emulsified asphalt is used as an example, with a fixed oil-water ratio of 60:40, that is, 60 kg of composite modified asphalt phase and 40 kg of aqueous soap solution.
[0039] <Example 1>
[0040] A modified emulsified asphalt based on reclaimed rubber undergoing induced oxidative degradation, comprising the following raw materials: 18 kg of reclaimed rubber (based on waste rubber powder), 6 kg of rubber oil, 0.04 kg of 2,2'-dibenzoylaminodiphenyl disulfide, 2.4 kg of SBS modifier, 0.06 kg of maleic anhydride, 0.072 kg of polyphosphoric acid, 33.468 kg of 70# base asphalt, 0.0167 kg of sulfur, 1 kg of emulsifier, and 39 kg of water and pH adjuster;
[0041] The preparation method of the above-mentioned reclaimed rubber composite modified emulsified asphalt includes the following steps:
[0042] S1. Preparation of high-dosage masterbatch: Waste rubber powder, rubber oil and 2,2'-dibenzoylaminodiphenyl disulfide were added to a reactor, heated to 180℃, air was introduced and sheared at 5000 r / min for 45 min to induce rubber degradation (the Mooney viscosity was measured to drop to between 15 and 18); then molten 70# base asphalt was added and shearing was continued for 30 min to obtain rubber-modified asphalt masterbatch;
[0043] S2. In-situ reaction: Add SBS modifier to the reactor, continue shear development for 1 hour, then cool to 160°C, add maleic anhydride and stir for 1.5 hours. After the system is stable, add polyphosphoric acid and stir at a constant temperature for 30 minutes.
[0044] S3. Interfacial micro-crosslinking anchoring: Sulfur was added to the system and stirred at 300 r / min at 160℃ for 2 h to prepare composite modified asphalt (oil phase), and its dynamic viscosity at 135℃ was tested.
[0045] S4. Shear emulsification: Heat water to 55°C, add emulsifier and adjust pH to 2.5 with hydrochloric acid to prepare 40kg soap solution. Then, pump the 150°C composite modified asphalt and soap solution into a colloid mill for shearing. The emulsion flowing out is immediately cooled to 65°C through a heat exchanger and discharged to obtain recycled rubber composite modified emulsified asphalt.
[0046] <Example 2>
[0047] A reclaimed rubber composite modified emulsified asphalt based on induced oxidative degradation, the raw materials used include 21 kg of reclaimed rubber (calculated as waste rubber powder), 7.5 kg of rubber oil, 0.04 kg of 2,2'-dibenzoylaminodiphenyl disulfide, 3 kg of SBS modifier, 0.06 kg of maleic anhydride, 0.078 kg of polyphosphoric acid, 28.362 kg of 70# base asphalt, 0.0156 kg of sulfur, 1.2 kg of emulsifier, and 38.8 kg of water and pH adjuster;
[0048] The preparation method of the above-mentioned reclaimed rubber composite modified emulsified asphalt includes the following steps:
[0049] S1. Preparation of high-dosage masterbatch: Waste rubber powder, rubber oil and 2,2'-dibenzoylaminodiphenyl disulfide were added to a reactor, heated to 190℃, air was introduced and sheared at 5000 r / min for 45 min to induce rubber degradation (the Mooney viscosity was measured to drop to between 15 and 18); then molten 70# base asphalt was added and shearing was continued for 30 min to obtain rubber-modified asphalt masterbatch;
[0050] S2. In-situ reaction: Add SBS modifier to the reactor, continue shear development for 1 hour, then cool to 165℃, add maleic anhydride and stir for 1 hour. After the system is stable, add polyphosphoric acid and stir at a constant temperature for 30 minutes.
[0051] S3. Interfacial micro-crosslinking anchoring: Sulfur was added to the system and stirred at 300 r / min at 165℃ for 1.5 h to prepare composite modified asphalt (oil phase), and its dynamic viscosity at 135℃ was tested.
[0052] S4. Shear emulsification: Heat water to 55°C, add emulsifier and adjust pH to 2.5 with hydrochloric acid to prepare 40kg soap solution. Then, pump the 160°C composite modified asphalt and soap solution into a colloid mill for shearing. The emulsion flowing out is immediately cooled to 65°C through a heat exchanger and discharged to obtain recycled rubber composite modified emulsified asphalt.
[0053] <Example 3>
[0054] A modified emulsified asphalt based on reclaimed rubber undergoing induced oxidative degradation, comprising the following raw materials: 24 kg of reclaimed rubber (based on waste rubber powder), 9 kg of rubber oil, 0.05 kg of 2,2'-dibenzoylaminodiphenyl disulfide, 3.6 kg of SBS modifier, 0.09 kg of maleic anhydride, 0.09 kg of polyphosphoric acid, 23.22 kg of 70# base asphalt, 0.0139 kg of sulfur, 1.4 kg of emulsifier, and 38.6 kg of water and pH adjuster;
[0055] The preparation method of the above-mentioned reclaimed rubber composite modified emulsified asphalt includes the following steps:
[0056] S1. Preparation of high-dosage masterbatch: Waste rubber powder, rubber oil and 2,2'-dibenzoylaminodiphenyl disulfide were added to a reactor, heated to 2000℃, air was introduced and sheared at 5000r / min for 45min to induce rubber degradation (the Mooney viscosity was measured to drop to between 15 and 18); then molten 70# base asphalt was added and shearing was continued for 30min to obtain rubber-modified asphalt masterbatch;
[0057] S2. In-situ reaction: Add SBS modifier to the reactor, continue shear development for 1 hour, then cool to 170°C, add maleic anhydride and stir for 0.5 hours. After the system is stable, add polyphosphoric acid and stir at a constant temperature for 30 minutes.
[0058] S3. Interfacial micro-crosslinking anchoring: Sulfur was added to the system and stirred at 300 r / min at 170℃ for 1 h to prepare composite modified asphalt (oil phase), and its dynamic viscosity at 135℃ was tested.
[0059] S4. Shear emulsification: Heat water to 55°C, add emulsifier and adjust pH to 2.5 with hydrochloric acid to prepare 40kg soap solution. Then, pump the 165°C composite modified asphalt and soap solution into a colloid mill for shearing. The emulsion flowing out is immediately cooled to 65°C through a heat exchanger and discharged to obtain recycled rubber composite modified emulsified asphalt.
[0060] <Comparative Example 1>
[0061] The difference from Example 2 is that the amount of sulfur used was increased to 0.056 kg, which is 0.2% of the mass of the base asphalt. As a result, during the development stage in step S3, the oil phase thickened rapidly and underwent macroscopic cross-linking, and the dynamic viscosity at 135°C soared to 4.8 Pa·s. When pumping through the colloid mill in step S4, it caused an overload alarm on the motor, and the colloid mill became severely clogged, making it impossible to complete emulsification.
[0062] <Comparative Example 2>
[0063] The difference from Example 2 is that step S3 is omitted, i.e., sulfur is not added. The rheological properties are excellent, with a dynamic viscosity of 0.55 Pa·s at 135°C, and emulsification is successfully completed. However, after standing for 24 hours, a distinct layer of black carbon black particles precipitates on the surface of the emulsion, indicating irreversible demulsification.
[0064] <Comparative Example 3>
[0065] The difference from Example 2 is that the induced degradation step in step S1 is removed; that is, 2,2'-dibenzoylaminodiphenyl disulfide is not added, and there is no aeration or shearing; all raw materials and excipients are directly physically mixed and blended. As a result, due to the extremely large steric hindrance, rubber agglomeration occurs under high shear, making it impossible to form a uniform fluid for subsequent emulsification.
[0066] Performance Testing
[0067] The emulsified asphalts of Examples 1-3 and Comparative Example 2 that were successfully prepared were tested in accordance with JTG E20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering", and the results are shown in Table 1.
[0068] Table 1 Performance Test Results
[0069] project Standard requirements Example 1 Example 2 Example 3 Comparative Example 2 Dynamic viscosity of the oil phase at 135℃ before emulsification (Pa·s) ≤1.0 0.78 0.86 0.95 0.55 Smoothness of wear / Extremely smooth Smooth Smooth Extremely smooth 1-day storage stability (%) ≤1.0 0.1 0.1 0.2 3.5 5-day storage stability (%) ≤5.0 0.4 0.6 0.9 Breast breaking Evaporation residue content (%) ≥55 60.3 60.1 60.4 / Softening point of residue (°C) ≥60 74 78 81 / Ductility of residue at 5°C (cm) ≥15 28 25 22 /
[0070] As can be seen from Table 1, after adopting the “induced degradation + PAA / MAH reconstruction + sulfur micro-crosslinking” process of this application, even if the rubber content is as high as 30-40%, the viscosity before emulsification can still be successfully controlled within the allowable range of over-grinding, and the final product has a 5-day storage stability of less than 1%, which is far better than the standard requirements, and completely overcomes the difficulty of easy stratification of high-content rubber emulsion.
[0071] The comparison between Comparative Example 1 and Example 2 demonstrates that the strict control of sulfur addition in this application produces unexpected technical effects; even a slight excess will lead to processing failure. The comparison between Comparative Example 2 and Example 2 demonstrates the indispensability of the "interfacial micro-crosslinking" mechanism in this application. Without this anchoring network of trace amounts of sulfur, while degradation alone facilitates processing, it significantly reduces storage stability. Comparative Example 3, compared to Example 2, demonstrates that without the induced degradation step, it is impossible to guarantee successful emulsification of high-dosage rubber. This is also the reason why non-degradation processes in the prior art can only produce low-dosage rubber or require granulation.
[0072] The embodiments described in this specific implementation are preferred embodiments of this application and are not intended to limit the scope of protection of this application. Therefore, all equivalent changes made in accordance with the structure, shape and principle of this application should be covered within the scope of protection of this application.
Claims
1. A method for preparing reclaimed rubber-modified emulsified asphalt based on induced oxidative degradation, characterized in that, Includes the following steps: S1. Preparation of high-content masterbatch: 30-40% of the total mass of the composite modified asphalt is mixed with the base asphalt and 10-15% of the total mass of the composite modified asphalt, and the mixture is subjected to high-speed shear swelling to prepare rubber modified asphalt masterbatch; the reclaimed rubber is a high-flowability reclaimed rubber with Mooney viscosity <20 obtained by heat-oxygen-chemical coupling induced oxidative degradation treatment of waste tire rubber. S2. In-situ reaction: Add 4-6% SBS modifier to the masterbatch, and after shear development, cool to 160-170℃. Add maleic anhydride to carry out in-situ grafting reaction. After the system is stable, add 0.12-0.15% polyphosphoric acid to adjust the pH value and rheological properties of the asphalt phase. S3. Interface micro-crosslinking anchoring: Sulfur is added to the system after S2 treatment, the amount of sulfur added is 0.05-0.06% of the mass of the base asphalt, and stirred at 160-170℃ for 1-2 hours to form a micro-crosslinking anchoring network between SBS, degraded reclaimed rubber and asphalt in the system without significantly increasing the macro viscosity, and the dynamic viscosity of the resulting composite modified asphalt at the emulsification temperature is controlled to be between 0.6-1.0 Pa·s; S4. Shear emulsification: Prepare a soap solution containing an emulsifier and water, wherein the mass of the emulsifier accounts for 1.0-1.4% of the total mass of the reclaimed rubber composite modified emulsified asphalt. The composite modified asphalt obtained in S3 is sheared together with the soap solution to obtain the reclaimed rubber composite modified emulsified asphalt.
2. The method for preparing reclaimed rubber-modified emulsified asphalt based on induced oxidative degradation according to claim 1, characterized in that, In step S1, the induced oxidative degradation process includes: mixing waste rubber powder with an oxidizing plasticizer and subjecting it to high-speed shearing at 180-200°C with air introduced, thereby inducing oxidative chain scission of rubber macromolecules; the oxidizing plasticizer is 2,2'-dibenzoylaminodiphenyl disulfide.
3. The method for preparing reclaimed rubber-modified emulsified asphalt based on induced oxidative degradation according to claim 1, characterized in that, In step S2, the maleic anhydride is directly added to the molten asphalt phase after the system is cooled to 160-170℃, and the reaction time is 0.5-1.5h.
4. The method for preparing reclaimed rubber-modified emulsified asphalt based on induced oxidative degradation according to claim 1, characterized in that, In step S3, the sulfur forms weak chemical bonds only at the phase interface, and the resulting network yield stress is greater than the buoyancy of the carbon black phase precipitating and floating in the reclaimed rubber, thereby suppressing the segregation phenomenon after emulsification.
5. The method for preparing reclaimed rubber-modified emulsified asphalt based on induced oxidative degradation according to claim 1, characterized in that, In step S4, the emulsifier is a cationic emulsifier and / or an amphoteric emulsifier.
6. The method for preparing reclaimed rubber-modified emulsified asphalt based on induced oxidative degradation according to claim 1, characterized in that, In step S4, the shearing process conditions are as follows: the temperature of the composite modified asphalt is controlled at 150-165℃, and the emulsion flowing out after emulsification is immediately cooled with circulating water so that its discharge temperature does not exceed 70℃.
7. The method for preparing reclaimed rubber-modified emulsified asphalt based on induced oxidative degradation according to claim 1, characterized in that, The base asphalt is either 70# heavy-duty asphalt or 90# heavy-duty asphalt for roads.
8. A reclaimed rubber composite modified emulsified asphalt prepared by the method of preparing reclaimed rubber composite modified emulsified asphalt based on induced oxidative degradation as described in any one of claims 1-7.
9. The reclaimed rubber composite modified emulsified asphalt based on induced oxidative degradation according to claim 8, characterized in that, The mass ratio of the asphalt phase to the water phase in the reclaimed rubber composite modified emulsified asphalt is 60:40, and the storage stability index of the reclaimed rubber composite modified emulsified asphalt after standing at room temperature for 5 days is ≤1.0%.
Citation Information
Patent Citations
An emulsified rubber asphalt material and a method for producing the same
CN114874459B
